Korupsi Dalam Perspektif Hukum Islam dan Strategi Pemberantasannya - Malthuf Siroj (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2016)
Corruption is an extraordinary crime because of its  negative impact on the aspects  of community life. People who have been infected by this deadly virus would die slowly but surely. This crime has a tremendous potential to cause misery, destitution and suffering of many people, especially the lower class people who do not have access to the power and economy; those who would have their rights only if they were given by the state. Corruption is a modern term whose synonym could not be found in the Islamic legal literature. However, by recognizing the elements contained, the term in Islamic criminal law is closely related to theft (sariqah), bribery (risywah), embezzlement of property (ghulul) and robbery (hirabah) with different legal sanctions. Corruption occurs because of many factors such as materialistic-consumerism lifestyle, costly political system, weak leadership, lack of religious and ethical education, social and legal systems that support corrupt behaviors. To eradicate corruption, repressive ways  can be done through the penal system as well as preventive efforts through non penal system.